Nutritional comparison between hydroponically grown leguminous and non-leguminous fodder to identify the adaptability and best harvesting time for sustainable hydroponic grass production (Research in Agriculture Livestock and Fisheries, 2022)
Two types of fodder crops were evaluated in this study, maize (Zia maize) and black gram (BG) (Vigna mungo) and in maize, non-descriptive local maize (LM) and hybrid maize (HM) verity were used. LM was considered as control and changes of the nutritional composition according to the type of fodder (leguminous and non-leguminous) and the day was evaluated. For comparative nutritional analysis, dry matter (DM), crude protein (CP), ether extract (EE), crude fibre (CF), acid detergent fibre (ADF), neutral detergent fibre (NDF), and total ash were analyzed and the biomass yield was measured using weight balance and root and shoot length of experimental fodders. Results revealed that among three types of forages total DM was significantly (P